Study and application of the energy unit cutting theory and punching-blasting synergy permeability enhancement technology in tectonic anomaly areas of coal mines - Jingyu JIANG; Xiaobin DONG; Mintao WEI; Chenghao WANG; Yuanping CHENG; Xiaoning SHI (Meitan xuebao)
The coal seams in tectonic anomaly areas have high gas content, high geostress, low permeability, the development of tectonic coal, and uneven distribution of disaster-causing energy. These areas are key for preventing and controlling coal and gas outburst accidents. Hydraulic/pneumatic punching technology is one of the main methods for gas drainage in tectonic coal. Compared to conventional drilling for gas extraction, it significantly increases the pressure relief radius. However, new stress concentration areas easily form between adjacent punching holes in the coal seam, limiting and affecting gas extraction. This paper combined theoretical analysis, numerical simulation, and field experiments, this study investigated the principles of energy reduction and outburst prevention using combined punching and controlled energy-accumulating blasting measures. The main conclusions of this paper are as follows: ① This paper proposes an Outburst Energy Unit Cutting theory and a punching-blasting synergistic permeability enhancement technology, combining with the distribution of outburst potential and outburst start-up energy criteria, dividing the coal seam into several energy units, and carrying out cutting at the boundary and internal zoning management. Essentially, this method involves punching holes first, followed by controlled energy-accumulating blasting to create directional fractures in the tectonic areas of the coal seam, releasing stress. The punched holes provide free space for the movement of coal within the impact range of the blasting injection, forming a free surface of the coal at the blasting injection point and altering the continuity of the coal seam. The generated explosive gases and directional stress waves can promote stress rebalancing. This alters the gradient of elastic and gas expansion energy in the coal body, effectively cutting the energy units in tectonic anomaly areas. ② The FALC3D numerical simulation shows that punching can reduce the stress in the coal around the hole. As the punching radius increases, the pressure relief radius also increases. After punching, a certain range of stress concentration forms outside the pressure relief zone around the hole, which limits gas flow. ③ The media-energy cutting principle of controlled directional cumulative blasting technology is clarified. The blasting changes the outburst potential occurrence gradient near the free surface of the coal of the cutting unit, realizing the media-cutting-controlled energy cutting. The unit cutting effectively increases the length of the energy-resistant zone in front of the mining work and reduces the risk of operation in the low-high energy transition zone. ④ A numerical model was constructed based on the fluid-solid coupling algorithm to simulate the synergistic effect of controlled directional energy-focused blasting and punching holes. Results indicate that controlled energy-accumulating blasting achieves directional fracturing of the coal seam, forming larger cracks in the energy concentration direction. Over time, radial crack networks form around the punched holes as the control hole, eventually connecting with cracks in non-energy concentration directions, effectively enhancing permeability in tectonic anomaly areas. ⑤ Field tests show that within a 10-meter range around the blasting hole, the stress and debris amount in the punched area of the coal body significantly decreases. The gas extraction volume after using single and double energy-focused tubes was 1.76 to 4.35 times and 1.35 to 8.60 times, respectively, compared to before blasting. The effective gas extraction radius of hydraulic punching was only 5 meters, while the synergistic pressure relief and permeability enhancement radius of punching and blasting were at least 10 meters, more than doubling the pressure relief radius in tectonic anomaly areas, and the monthly driving speed of coal roadway has been increased by about 20 m per month.